Persepsi Dosen dan Mahasiswa Program Studi Informasi Perpustakaan dan Kearsipan Fakultas Bahasa dan Seni Universitas Negeri Padang terhadap Wikipedia sebagai Sumber Informasi Digital Ilmiah - Syafrita, Erdiana; Ardoni, Ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
Abstract Based on the research of the study. It can be concluded as follows. IPK lecturers perception of Wikipedia as a scientific digital information source. 1) Perception of Wikipedia knowledge and understanding. Most of IPK lecturers and students know the advantages and disadvantage of Wikipedia. 2) perception of Wikipedia usage and access indicators. Most of IPK lecturers and students often access and used Wikipedia, including in making scientific works. 3) IPK lecturers and students perceptions of assessment indicators in the use of Wikipedia as a scientific digital information source. Assessment indicators in Wikipedia accuracy. Many of IPK lecturers and students stated that Wikipedia is quite accurate as a digital scientific information source.Keywords: perception; digital information; Wikipedia.